Implementasi Blockchain dalam Meningkatkan Transparansi dan Kepercayaan pada Lembaga Wakaf di Indonesia - Dewi Kurniasari; Sholikul Hadi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the implementation of blockchain technology in enhancing transparency and public trust in waqf institutions in Indonesia. The research employs a qualitative approach using literature study and conceptual analysis methods based on various scientific journals, regulations, institutional reports, and recent blockchain literature. The results indicate that blockchain possesses characteristics such as decentralization, immutability, transparency, and smart contracts, which can strengthen the governance of waqf institutions. The implementation of blockchain enables real-time recording of waqf transactions, improves accountability in asset management, and expands public participation in digital waqf. The study also finds that low transparency and weak reporting systems are the main factors contributing to the decline of public trust in some waqf institutions. Blockchain technology can serve as a strategic solution by providing a secure and transparent public verification mechanism. However, the implementation of blockchain in Indonesia still faces challenges, including regulatory issues, limited digital infrastructure, high system development costs, and low human resource competence. This study recommends strengthening digital waqf regulations, improving technological literacy, and fostering synergy among the government, waqf institutions, academics, and technology companies in developing a blockchain-based digital waqf ecosystem in Indonesia.